Abdul Wahid Hasyim's Thoughts in Modernizing Islamic Education Institutions in Indonesia - Saefrudin Saefrudain (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2023)
Islamic educational institutions are the nation's bastions that are consistent in caring for the nation's morals, with Islamic values. Islamic educational institutions have the role of organizing religion-based learning, but nowadays, with the demands of the times and the rapid development of science and technology, they are also required to provide general knowledge. Because K.H. Abdul Wahid Hasyim in developing and advancing Islamic educational institutions in Indonesia must be adapted to the needs of present and future society. In this study, the researchers put more emphasis on the aspect of how K.H. Abdul Wahid Hasyim modernized Islamic educational institutions in Indonesia, both elementary, secondary, and tertiary education, the purpose of which is for these institutions to be able to develop, progress and exist in an era of changing times that are so fast. The findings from this study are that K.H. Abdul Wahid Hasyim has forward-thinking ideas in modernizing Islamic educational institutions in Indonesia, including integrating religious and general curricula, establishing libraries as a source of knowledge, increasing motivation to study and writing, establishing higher quality Islamic educational institutions, reforming religious department institutions, improving courts religion and reforming the rituals of Hajj and Umrah